Liver transplantation in Jehovahʼs Witnesses at Santa Isabel Hospital in Blumenau – Santa Catarina: Survey of data from medical records - Nogara, Marcelo Augusto Scheidemantel (2021)
Purpose: To collect data on the occurrence of liver transplants in Jehovah's Witnesses in Hospital Santa Isabel, Blumenau city, state of Santa Catarina. Methods: This is a cross-sectional observational study, which the inclusion criteria were patients from a specific religious group (Jehovah's Witnesses), who due to religious precept, do not accept blood transfusion and liver transplantation, from September 2006 to June. 2019. The study was conducted by analyzing 22 medical records, 21 of which were studied due to the completeness of the information, evidencing the epidemiological data (age, gender, city of origin and pathology), MELD score and need for intra and post-operative blood transfusion. Such collection was performed from August to October 2019. Results: The average age of the transplanted patients was of 53-54 years old, being the majority of male gender (61.9%; n=13). The prevalent etiology was Hepatitis C (HCV) liver cirrhosis with no hepatocarcinoma (38.9%; n=8). From the 21 patients studied, 9 are from Santa Catarina state (40.9%), and 12 from six other Brazilian states (57.14%). In the MELD assessment, 33.33% (n=7) of patients were classified as lower than 15, 52.38% (n=11) with MELD between 15 and 25, and 14.28% (n=3), higher than 25. Only 3 transplanted (14.28%) required blood element transfusion. Conclusion: This study demonstrates that the HSI service is a national reference for organ transplantation, with an increasing number of patients coming from other Brazilian states. Furthermore, the procedure shows great success among Jehovah's Witness patients, since among the 21 analyzed, only 3 required the use of a blood-derived product.